From juvenile to adult: investigating miRNAs, gene expression, and the juvenile cone in olive development - Romero-Rodríguez, Paola; Gordon, Ana; Meca, Esteban; Tercero-Alcázar, Carmen; Martin, Galen T.; Garcia-Lopez, M. Teresa; Moral, Juan; Gaut, Brandon S.; Diez, Concepción M. (Frontiers in Plant Science, 2025)
The long juvenile phase in perennials hinders rapid breeding, highlighting the need for early selection markers. Some species, such as the olive tree (Olea europaea L.), develop a juvenile cone, where adult tissue forms in the upper and peripheral canopy, while basal and inner regions remain juvenile. These structures offer a unique, yet underexplored, system for studying the juvenile-to-adult transition while minimizing genetic and environmental variability. We analyzed tissues from trees with a juvenile cone to identify genes and miRNAs distinguishing juvenile from adult vegetative tissue. Known transition markers, including miR156, miR172, and homologs of APETALA2 and AGAMOUS-like 42, showed clear differential expression across developmental stages, with the miR156/miR172 ratio being particularly discriminatory. In contrast, DNA methylation patterns showed few differences between juvenile and adult leaves, and differentially expressed genes were not enriched for methylation changes. Our findings show that the juvenile cone represents an intermediate developmental stage and provides a unique system for studying phase transitions in perennials. Identified miRNA and gene markers not only improve our understanding of olive development but also offer practical tools to facilitate the selection of rapid-maturing genotypes in olives and other perennials, such as pistachio (Pistacia vera L.). Overall, the juvenile cone serves as a valuable model for developmental analyses, and our findings provide a framework to enhance breeding efficiency in olives and other perennial fruit species.